Research progress of perioperative airway management in elderly patients with lung cancer (老年肺癌患者围手术期呼吸道管理研究进展) - TAO Fang (陶芳); ZHOU Ting (周婷) (中西医结合护理)
The senile patients with lung cancer are more likely to be complicated with pneumonia, atelectasis and even respiratory failure after operation. The perioperative airway management is closely related to the postoperative pulmonary complications, and high-quality airway management helps to improve the recovery of postoperative pulmonary function and quality of life. This article reviews the contents and progress of airway management in elderly patients with lung cancer in recent years, in order to provide reference for clinical medical workers to carry out airway management in perioperative period. (老年肺癌患者术后易发生肺炎、肺不张甚至呼吸衰竭等并发症。围手术期的呼吸道管理与术后肺部并发症的发生密切相关, 优质的呼吸道管理措施有助于提高患者生活质量, 改善患者术后肺功能。本研究对近年来我国老年肺癌患者围手术期呼吸道管理的内容及进展进行了综述, 旨在为临床医务工作者开展老年肺癌患者围手术期呼吸道管理工作提供参考。)